2017
DOI: 10.1038/srep40030
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin protects the respiratory system from PM2.5 exposure

Abstract: Atmospheric particle is one of the risk factors for respiratory disease; however, their injury mechanisms are poorly understood, and prevention methods are highly desirable. We constructed artificial PM2.5 (aPM2.5) particles according to the size and composition of actual PM2.5 collected in Beijing. Using these artificial particles, we created an inhalation-injury animal model. These aPM2.5 particles simulate the physical and chemical characteristics of the actual PM2.5, and inhalation of the aPM2.5 in rat res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Actually, several in vivo studies have reported an important protective role of polydatin treatment via different mechanisms in ovalbumin-induced bronchial asthma as well as in LPS-induced acute lung injury [212,213]. Moreover, polydatin protects the respiratory system from the damage caused by fine particulate matters (aerodynamic diameter < 2.5 μm; PM2.5) during air pollution that may cause deleterious effects such as premature death among individuals due to lung disease, lung dysfunction and asthma exacerbation, mainly by the capacity of polydatin to reduce the injury from oxidative stress and inflammation in lung tissues [214]. Moreover, polydatin can attenuate hypoxic pulmonary hypertension through Protein Kinase C Mechanisms (PKC) and it might be a promising candidate for hypoxic pulmonary treatment [215].…”
Section: Polydatinmentioning
confidence: 99%
“…Actually, several in vivo studies have reported an important protective role of polydatin treatment via different mechanisms in ovalbumin-induced bronchial asthma as well as in LPS-induced acute lung injury [212,213]. Moreover, polydatin protects the respiratory system from the damage caused by fine particulate matters (aerodynamic diameter < 2.5 μm; PM2.5) during air pollution that may cause deleterious effects such as premature death among individuals due to lung disease, lung dysfunction and asthma exacerbation, mainly by the capacity of polydatin to reduce the injury from oxidative stress and inflammation in lung tissues [214]. Moreover, polydatin can attenuate hypoxic pulmonary hypertension through Protein Kinase C Mechanisms (PKC) and it might be a promising candidate for hypoxic pulmonary treatment [215].…”
Section: Polydatinmentioning
confidence: 99%
“…Thanks to these properties, polydatin is frequently used for treating health-related disorders such as cardiac disabilities ( 20 ), various carcinomas ( 21 , 22 ), hepatitis ( 23 ) and hepatic fibrosis ( 24 ). It can also significantly reduce lipopolysaccharide-induced lung injury ( 25 ), protect against PM2.5-induced respiratory system diseases ( 26 ) and alleviate reactive oxygen species (ROS)- and bleomycin (BLM)-induced EMT and pulmonary fibrosis ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polydatin (PD), a resveratrol glucoside, is abundant in different daily nourishment such as red wines, grapes as well as cocoa-containing products. 15,16 Despite the identification of diverse beneficial functions of resveratrol (RSV) (eg anti-inflammation, antioxidant and anti-ageing), RSV does not exert favourable pharmacological properties because of its quick clearance rate and poor oral bioavailability. 17,18 Therefore, it is essential to search novel molecules that have extensive pharmacological protective effects beyond RSV.…”
Section: Introductionmentioning
confidence: 99%